Human Research Methodology - Quoc, Nguyen Anh; Y, Nguyen Van; Giau, Huynh Van (Journal of Ecohumanism, 2024)
Scientific research methods are essential. Each science has its subject matter and different methodologies that produce different cognitive results. Science is human life, however, science becomes a metaphysical theory, it is governed by the methodology of philosophy in history or mathematics. Philosophy and mathematics are theoretical sciences, making the related sciences into models, ideals, and pure reason. The inability of science becomes human misfortune, science becomes strange to people. True science starts from human life and becomes a methodology for researching related scientific disciplines. When studying the outside world, people uphold the principles of objectivity, comprehensiveness, development, specific history, and practice. When studying life, the object is perceived that human beings are living in the process of creating abilities and needs that make life rich and diverse. Humans are both the subject and the object of scientific research. Interdisciplinary sciences have in common that they take human life as the object of research.